Fish choruses off Port Hedland, Western Australia. Issue 2 (4th May 2017) - Parsons, Miles J. G.; Salgado Kent, Chandra P.; Recalde-Salas, Angela; McCauley, Robert D.
Abstract: Australian waters are home to a number of vocal species of fish. Cataloguing the acoustic characteristics and temporal patterns of choruses and their locations can provide significant information for long-term monitoring of vocal fishes and their ecosystems. In coastal waters off Port Hedland, Western Australia, two seafloor positioned sea-noise loggers, located 21.5 km apart in 8 and 18 m of water, recorded for an 18-month period. Numerous sound sources were detected, including mooring and vessel noise, humpback whale song and a large variety of fish signal types. Seven fish choruses were identified, occurring predominantly between late spring and early autumn (wet season) and displaying energy from 50 Hz to >4 kHz. Many of these choruses exhibited acoustic characteristics similar to choruses previously reported elsewhere, for some of which the source species or families have been identified. Distinct diurnal patterns in the choruses were observed, associated with sunrise or sunset and in some cases, both. While choruses were predominantly recorded on different days, there were at total of 80 days when more than one chorus was present at the same site. Some pairs of choruses present on the same day exhibited various combinations of temporal and frequency partitioning, while others displayed predominant overlap in both spaces.